The Implementation of Independent Learning-Independent Campus in the Guidance and Counseling Study Program - Rachman, Ali; Setiawan, Muhammad Andri; Putro, Hendro Yulius Suryo (Bisma The Journal of Counseling, 2022)
The Minister of Education and Culture of the Republic of Indonesia has issued a policy of independent learning on independent campuses. This policy aims to improve the competence of graduates, both soft skills and hard skills, encourage students to master various sciences, students are better prepared to enter the world of work. The purpose of this study was to determine the implementation of the independent campus learning program in the Guidance and Counseling Study Program FKIP ULM. This type of research is descriptive qualitative. The data is taken in research through literature study. The results of the analysis show that the concept of independent learning in independent campuses is manifested in the form of activities, namely student exchanges, internships or work practices, teaching assistance in education units, research, humanitarian projects, entrepreneurial activities, independence projects, and real work lectures on village development. The implementation of the independent campus learning program in the Guidance and Counseling Study Program FKIP ULM is carried out through three learning activities, namely teaching assistance in education units, internships or work practices, and student exchanges.